PENAMBAHAN METIL TESTOSTERON DALAM PAKAN UNTUK MEMACU PERTUMBUHAN NILA MERAH (Oreochromis sp.) - Susilo Budi Priyono (Jurnal Perikanan Universitas Gadjah Mada, 2003)
The experiment was carried out to know the effect of supplemental dietary 17 methytetosterone (MT) on growth enhancement of red tilapia (Oreochromissp.). Fry smaller than 14 mm was given MT at 0 (control) and 60 mg/kg of feed for 28 days for masculinization. After masculinization, the fish were fef with MT at 0 (control), 1, 5, and 10 mg/kg of feed for 60 days to enhance the growth. The results showed that masculinization using MT at high dosage (60 mg/kg) was able to produce 96% of males fry at low dosage (1 – 10 mg/kg) also enhanced the growth of fishes. The highest growth rate 30% was observed at 10 mg MT/kg of feed. The growth enhancement was more effective in masculinized fry.